LINGUISTIC FEATURES FOR A LANGUAGE LEARNING RESEARCH: The Case of Passives and Medio-Passives in English - Jufrizal Jufrizal (English Language Teaching and Research, 2017)
Conducting a research on EFL learning may be initiated by students’ problems in understanding linguistic-grammatical features of the learnt language. Therefore, students’ problems and difficulties in understanding English grammatical features can be the sources of problems of language teaching researches. This paper, which is practically derived from experiences of teaching English grammar and conducting researches in 2009 and 2012, particularly discusses how to derive the linguistic-grammatical features of English become the topic/research problem of researches on EFL learning. By using the case of passives and medio-passives of English, the discussion presented in this paper specifically is the answer for questions: (i) why do passives and medio-passives of English become academic problems for most Indonesian learners?; and (ii) how can the linguistic features of English passives and medio-passives be derived as a topic/research problem of EFL learning? The data presented in this paper are those collected through researches conducted in 2009 and 2012, and supported by others picked up during the teaching-learning processes of English Grammar subject at the English Department of Universitas Negeri Padang. The idea of this paper may give scientific information to the researchers in order to derive and to develop topics and/or research problemsof EFL learning. Key words: linguistic features, language teaching, research, passives, medio-passives